Optical solitons of the coupled nonlinear Schrodinger's equation with spatiotemporal dispersion - İnç, Mustafa; Ates, Esma; Tchier, Fairouz (Springer, 2016)
In this work, the coupled nonlinear Schrodinger's equation (CNLSE) is studied with four forms of nonlinearity. The nonlinearities that are considered in this paper are the Kerr law, power law, parabolic law and dual-power law. Jacobi elliptic function solutions and also bright and dark optical soliton solutions are obtained for each law of the CNLSE. We will acquire constraint conditions for the existence of obtained solitons.
Keywords: Solitons; Jacobi elliptic functions; Non-Kerr nonlinearity; Optical couplers